MOLECULAR CHARACTERIZATION AND PHYLOGENETIC ANALYSIS OF CLARIAS GARIEPINUS AND CLARIAS BATRACHUS USING DNA BARCODING TECHNIQUES - JAYASWAL, RAJESH; RAJANNA, K.B.; DAS, BASANTA KUMAR; M R, BHAVANJALI; MAURYA, NARENDRA KUMAR; SINGH, DEEPENDRA; MANDAL, BISWAJIT (Journal of the Inland Fisheries Society of India, 2024)
DNA barcoding has emerged as a reliable method for the rapid and accurate identification of animal species, leveraging genomic sequences to distinguish between closely related species. This study focuses on the molecular characterization of Clarias gariepinus and Clarias batrachus, two economically significant catfish species, using cytochrome c oxidase I (COI) and 16S rRNA genes. pecimens of C. gariepinus and C. batrachus were identified based on morphometric traits, specifically gill-raker counts (GRC). DNA from preserved tissue samples was amplified using COI and 16S rRNA primers. Genetic divergence and phylogenetic trees were used to determine species connections. C. batrachus COI and 16S rRNA genes have genetic distances of 0.141 and 0.077, whereas C. gariepinus had 0.140 and 0.047. Three COI clades were found in C. batrachus and C. gariepinus by phylogenetic analysis. The 16S rDNA sequences divided      C. batrachus and C. gariepinus into three groups, with C. dussumieri closely linked to B. bagarius (KT878055) with an 82% bootstrap score. The K2P/NJ tree analysis supported the clustering of similar species and confirmed the taxonomic groupings observed. DNA barcoding, using the COI and 16S rRNA genes, distinguishes C. gariepinus and C. batrachus, two closely related fish species. C. gariepinus and the Asian Clarias species evolved separately, demonstrating the significance of DNA barcoding in species identification and phylogenetic study. COI gives valuable insights; however, DNA barcoding and morphological data provide a more complete picture of fish biodiversity and fisheries sustainability.